2010
DOI: 10.1007/s12649-009-9003-0
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Printed Circuit Boards from Waste Electrical and Electronic Equipment by Pyrolysis

Abstract: Waste electrical and electronic equipment waste generated in the European Union (EU27) has been identified as one of the fastest growing waste streams in the EU, such that by 2020 annual arisings of waste electrical and electronic equipment will be 12.3 million tonnes. The EU have introduced the Waste Electrical and Electronic Equipment (WEEE) Directive which aims to promote the re-use, recycling and other forms of recovery of electrical and electronic waste. Printed circuit boards represent a particular categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(19 citation statements)
references
References 68 publications
1
17
0
1
Order By: Relevance
“…biphenyl and triphenylene), as well as methylated benzofurans and naphthalenes. The emitted phenol compound had the highest yield in the PCBs pyrolysis (Williams, 2010) because it is present in the epoxy resin.…”
Section: (Figure 4)mentioning
confidence: 99%
“…biphenyl and triphenylene), as well as methylated benzofurans and naphthalenes. The emitted phenol compound had the highest yield in the PCBs pyrolysis (Williams, 2010) because it is present in the epoxy resin.…”
Section: (Figure 4)mentioning
confidence: 99%
“…Williams [16] in a recent review paper reported the use of pyrolysis for the treatment of wastes from electronic printed circuit boards as a recovery method for useful products such as metals, liquid and gaseous products as well as glass fibres. He also stated that the circuit boards contain significant concentrations of bromine in the form of bromine containing flame retardants, which also appears in the liquid fraction in the form of brominated organic compounds, a property which could possibly affect the the potential end uses of the produced oil.…”
Section: Chemical and Thermo-chemical Recycling Methodsmentioning
confidence: 99%
“…About 2 to 5% Sb is usually used in Pb-Sn-Sb alloys [6]. Antimony, found predominantly in printed circuit boards, is known to be toxic and highly volatile [9].…”
Section: Antimonymentioning
confidence: 99%